Effects of a new antiarrhythmic drug SS-68 on electrical activity in working atrial and ventricular myocardium of mouse and their ionic mechanisms - Saida K. Bogus; Denis V. Abramochkin; Pavel A. Galenko-Yaroshevsky; Konstantin F. Suzdalev (Elsevier, 2015)
SS-68 is a derivative of indole, which demonstrated strong antiarrhythmic effects not associated with significant QT prolongation in dog models of atrial fibrillation. Therefore, SS-68 was proposed as a new antiarrhythmic drug and the present study is the first describing its effects on action potentials (APs) configuration and elucidating the ionic mechanisms of these effects. Sharp microelectrodes were used to record APs in isolated preparations of mouse atrial and ventricular myocardium. In both types of myocardium 10−6 M SS-68 produced reduction of AP duration, 3 × 10−6 M failed to alter AP waveform and 10−5 - 3 × 10−5 M prolonged APs. Sensitivity of main ionic currents to SS-68 was determined using whole-cell patch clamp. Transient potassium current Ito was slightly inhibited by SS-68 with IC50 = 1.43 × 10−4 M. IKur was more sensitive with IC50 = 1.84 × 10−5 M. Background inward rectifier showed very low sensitivity to SS-68 - only 10−4 M SS-68 caused significant reduction of IK1. ICaL was significantly inhibited by 10−6M - 3 × 10−5 M SS-68. The IC50 value for the ICaL was 1.84 × 10−6 M. Thus, main ionic currents of mouse cardiomyocytes are inhibited by SS-68 in the following order of potency: ICaL > IKur > Ito > IK1. While lower concentration of SS-68 shorten APs via suppression of ICaL, higher concentrations inhibit K+-currents leading to APs prolongation.